ANALISIS MODAL SOSIAL PADA KEBERDAYAAN PETANI KARET (Studi Kasus Petani Karet Di Kecamatan Logas Tanah Darat Kabupaten Kuantan Singingi) - ', Junaidi; ', Rosnita; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research are: 1) Analyzing social capital owned rubber growers in  Logas           Tanah  Darat             subdistrict of    Kuantan Singingi; 2) Analyzeempowerment rubber farmers in the Logas Tanah Darat subdistrict of Kuantan Singingi. This research was conducted in Logas Tanah Darat subdistrict of Kuantan Singingi starting on March to December 2015, this research was using survey methods of determining the sampling is specifiedPurpossive Sampling with the consideration that the people are planting rubber and largely incorporated in the farmers group, the number of respondents as much as 97 people were taken from the Perhentian Luas and Sikijang village. Data analysis using the method of the scale Likert.The results of this research showed that are: 1) Social capital rubber farmers in Logas Tanah Darat Subdistrickt the categored very high. 2) The empowerment of rubber farmers in Logas Tanah Darat Subdistrict the categoredquite empowerment.To the members of the Group of farmers in order to maintain the social capital that is owned by farmers will tend to empowerment so that the better and vice versa if the social capital of the farmer declined then empowerment rubber farmers will tend to get worse, Farmers group members to follow the activities of the development of the idea or the concept of farming that has been going on that are considered true and important, and always follow the farmers group activities in order to improve empowerment  rubber farmers in the Logas Tanah Darat Subdistrict,  to the Government to give attention for Community area in improve the economy by giving programs that are empowering communities aimed at the advancement of the Community area. Keywords: SocialCapital, Empowerment, Rubber Farmers.